Peningkatan Kualitas Pengelolaan Sampah Berkelanjutan Melalui Edukasi Pentingnya Menjaga Lingkungan - Novriyanto Napu; Titien Fatmawaty Mohammad; Sri Manovita Pateda (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2025)
The problems of waste are not only in Indonesia, but throughout the world. Waste production continues to increase along with population growth, changes in consumption patterns and people's lifestyles. This article discusses efforts to improve infrastructure quality through sustainable waste management with education about the importance of protecting the environment at SDN 11 Batudaa Pantai, Lamu Village. This research aims to increase environmental awareness among students through Real Work Lecture (KKN) activities. The method used includes three stages: preparation, implementation of educational and practical programs, and evaluation. Activities include education about types of waste, including making crafts from waste and waste management practices, including making crafts from organic and inorganic waste. The results show that students initially did not understand the types of waste and the 3R concept (Reduce, Reuse, Recycle). However, after education, they showed better understanding and increased motivation to keep the environment clean. It is hoped that this program can become an example for sustainable waste management and improving environmental quality in the future.